2017
DOI: 10.1016/j.bjm.2016.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Grazing of particle-associated bacteria—an elimination of the non-viable fraction

Abstract: Quantification of bacteria being grazed by microzooplankton is gaining importance since they serve as energy subsidies for higher trophic levels which consequently influence fish production. Hence, grazing pressure on viable and non-viable fraction of free and particle-associated bacteria in a tropical estuary controlled mainly by protist grazers was estimated using the seawater dilution technique. In vitro incubations over a period of 42 h showed that at the end of 24 h, growth coefficient (k) of particle-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…on Aeromonas hydrophila over Pseudomonas fluorescens[10] . One recent study suggested that protozoa preferentially graze non-viable and particle-associated forms over viable and free cells[11]. Another paper indicated that Tetrahymena sp.…”
Section: Introductionmentioning
confidence: 99%
“…on Aeromonas hydrophila over Pseudomonas fluorescens[10] . One recent study suggested that protozoa preferentially graze non-viable and particle-associated forms over viable and free cells[11]. Another paper indicated that Tetrahymena sp.…”
Section: Introductionmentioning
confidence: 99%